2021
DOI: 10.3390/jcm10081707
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Completion Thyroidectomy via the Bilateral Axillo-Breast Approach

Abstract: Background: Bilateral axillo-breast approach (BABA) robotic thyroidectomy has been successfully performed for thyroid cancer patients with excellent cosmetic results. Completion thyroidectomy is sometimes necessary after thyroid lobectomy, and whether it has a higher complication rate than the primary operation due to the presence of adhesions remains controversial. The aim of this study was to evaluate surgical outcomes, including operation time and postoperative complications, in patients who underwent BABA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
(8 reference statements)
0
17
0
Order By: Relevance
“…Of the studies included in this article, completion thyroidectomy was described by eight studies, using all mentioned techniques except the RA-ET and RA-RT (31,34,41,43,46,57,65,89). Moreover, several other studies described the safety and feasibility of minimally invasive techniques for the completion thyroidectomy, showing the vast range of application of these techniques (65,(120)(121)(122). It is advised to either perform re-operation within two weeks after initial surgery or after two to three months to minimize complications due to adhesions (57,65,120).…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies included in this article, completion thyroidectomy was described by eight studies, using all mentioned techniques except the RA-ET and RA-RT (31,34,41,43,46,57,65,89). Moreover, several other studies described the safety and feasibility of minimally invasive techniques for the completion thyroidectomy, showing the vast range of application of these techniques (65,(120)(121)(122). It is advised to either perform re-operation within two weeks after initial surgery or after two to three months to minimize complications due to adhesions (57,65,120).…”
Section: Discussionmentioning
confidence: 99%
“…BABA RT is one of the most popular remote-access approaches for thyroid surgery ( 22 ). Several studies have revealed that BABA robotic completion thyroidectomy could be performed safely without completion-related complication ( 22 , 23 ). The experiences of utilizing BABA RT in lateral neck dissection have been shared in a few studies ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…The time interval between the two surgeries exceeded 2 weeks in three patients, and there was no open conversion. Similar experience from the bilateral axillo-breast approach also revealed a 100% success rate in 33 consecutive patients who underwent completion thyroidectomy through the same route [ 66 ]. The mean interval between the two surgeries was 5.5 months in their study.…”
Section: Special Considerationmentioning
confidence: 97%